Against the Tarbiyah’s Symbolism of Hijab: Feminism, Islamic Conservatism and Reconstruction of Hijab Symbolism in Indonesia - Ayu Regina Yolandasari (Journal of Asian Social Science Research, 2021)
Although Indonesia is the largest Muslim country in the world, the way of how Muslims dress had never been a major focus of Islamic practice until the 1980s. The promotion of a particular Islamic dress code, especially hijab (veil), started in the early 1980s on Indonesian campuses. Since the Reformasi in 1998, the wearing of hijab has grown significantly along with the spread of the Tarbiyah movement, a transnational Islamist movement affiliated with the Muslim Brotherhood from Egypt. The rise of Islamic conservatism has targeted women to be controlled through their dress and caused Indonesian women to lose their freedom to decide whether they want to wear hijab or not. To fully understand this controlling mechanism, this article explores how the Tarbiyah movement has constructed and utilized the symbolization of hijab, and the weakness of the movement in enforcing its conservative values to its Muslim women members. Such exploration may direct us to a counter-strategy against the values. Based on in-depth interviews with four former Tarbiyah activists who have been active in feminism, this article examines the way the Tarbiyah controls its female activists through the hijab symbolization and how feminism has helped these activists to detach themselves from the movement. Thus, this article will make an important point on how feminism contributes to the battle against Islamic conservatism in Indonesia.